“The job changes you”: a reflexive thematic analysis of Australian correctional officer mental health - Miller, Olivia (Journal of crime and justice, 2024)
Correctional officers (COs) work under stressful conditions and experience high rates of potentially psychologically traumatic critical incidents, and yet understanding of their mental health is limited. Therefore, the current study aimed to explore how correctional work impacts CO mental health. Twenty-two Australian COs (12 men, 10 women) working predominantly in high security prisons (91%) with male prison residents (50%) were interviewed about their mental health and workplace experiences. Reflexive thematic analysis of these interviews generated three key themes: the job changes you, it’s a stressful job, and coping strategies. Officers showed both positive and negative changes to their sense of self, daily functioning, and mental health which were generally consistent with experiences of psychological wellbeing, posttraumatic growth, and burnout. These changes were impacted by a variety of operational and organizational stressors and were managed through adaptive and maladaptive coping strategies like social support, humor, and alcohol consumption. The findings support existing theories of the non-dichotomous nature of mental health and mental illness. Along with deepening understandings of CO mental health, this study provides guidance on how COs can be supported to be healthy and productive in the workplace.